2015
DOI: 10.3109/13645706.2015.1117494
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gastro-jejunal anastomosis using novel r2 deflectable instruments in anex vivomodel

Abstract: This study demonstrates the ease of use, efficacy of manipulation and swift training effect with the novel r2 instruments for both experienced laparoscopic surgeons and untrained non-surgeons. After few cases stable anastomosis times and a fast learning curve were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Loss of instrumental control provided fatigue and disappointment leading to the abandonment of procedures in the novices [19]. The physical and mental workload for laparoscopic surgeons might be counterproductive for the operative time and quality of hand-sewn anastomoses or other demanding procedures [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of instrumental control provided fatigue and disappointment leading to the abandonment of procedures in the novices [19]. The physical and mental workload for laparoscopic surgeons might be counterproductive for the operative time and quality of hand-sewn anastomoses or other demanding procedures [20].…”
Section: Discussionmentioning
confidence: 99%
“…We can speculate that experienced surgeons were more familiar with the traditional techniques and developed less adaption in changing suture techniques. In fact, in a laparoscopic gastro-jejunal anastomosis study, the use of a novel deflectable instrument in an ex vivo model demonstrated a fast learning curve for all participants, but the learning curve of novices was even more rapid [20]. In that study, even though the anastomosis time of the novices came closer to that of trained surgeons after a number of trials, the statistical analysis revealed that the average suturing times and the complete anastomosis times were still expectably different when comparing the fifth trial of the untrained to experienced participants.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a high BMI, the mobility of the 2 mm instruments is significantly restricted due to the thick abdominal wall. To overcome the limitation of the current operation a further development of 2 mm instruments with a higher rigidity or steerability may be required (10).…”
Section: Discussionmentioning
confidence: 99%